A novel interactive technique for load current harmonic reduction for any randomly utilized household equipment - Eman Farag Ahmed; EL-Sayed Soliman A. Said; Hala M. Abdel Mageed; Abdelhady Abdelazim Ammar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Sustaining a stable level of power quality in the localized network is a growing challenge due to the increased use of power electronics. This paper proposes a novel interactive technique that reads the load current according to the connected loads. Whenever equipment is started running, the system is immediately read the distorted current for three cycles. The fundamental current can be estimated according to the system acquired readings. This system subtracts this estimated fundamental current from the sensor current reader to extract the total harmonic currents. According to the total harmonic currents the system uses suitable switching frequency Fs and modulation index Ma for generating anti-current source inverter (CSI) pulse width modulation (PWM) signal. Complete and comprehensive comparison between the system laboratory measurements using the Calmet TE30 power analyzer and the simulation model are presented. These results confirmed significant agreements between the proposed model and actual measurements at different loads. Furthermore, current and voltage sensors accompanied with a microcontroller read the load current the system realization. Finally, the measured currents of different loads are almost typically confirmed with the power analyzer's results. The reduced harmonics currents of the implemented model display the system validation.